2014
DOI: 10.1371/journal.pone.0109032
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Text Message Reminders on Adherence to Antimalarial Treatment in Northern Ghana: A Randomized Trial

Abstract: BackgroundLow rates of adherence to artemisinin-based combination therapy (ACT) regimens increase the risk of treatment failure and may lead to drug resistance, threatening the sustainability of current anti-malarial efforts. We assessed the impact of text message reminders on adherence to ACT regimens.MethodsHealth workers at hospitals, clinics, pharmacies, and other stationary ACT distributors in Tamale, Ghana provided flyers advertising free mobile health information to individuals receiving malaria treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 17 publications
1
62
1
1
Order By: Relevance
“…10 Text-messaging programs offer a promising new platform to improve sexual and reproductive health, in particular among adolescents, by providing information in a private and confidential way. The past decade has seen a rapid rise in text-messaging programs that aim to improve health [11][12][13] ; however, systematic reviews have consistently found a dearth of high-quality peer-reviewed studies examining outcomes of these programs in LMICs. [14][15][16][17] Despite a large number of recent projects leveraging mobile technology among adolescent populations in LMICs, none of these employs a randomized trial design to provide evidence of effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…10 Text-messaging programs offer a promising new platform to improve sexual and reproductive health, in particular among adolescents, by providing information in a private and confidential way. The past decade has seen a rapid rise in text-messaging programs that aim to improve health [11][12][13] ; however, systematic reviews have consistently found a dearth of high-quality peer-reviewed studies examining outcomes of these programs in LMICs. [14][15][16][17] Despite a large number of recent projects leveraging mobile technology among adolescent populations in LMICs, none of these employs a randomized trial design to provide evidence of effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…private retail sector. 8,18,45 (There was no evidence that adherence increased over the course of the study, which suggests that Hawthorne effects were relatively minor in this sample.) We also found that a positive result on the RDT did not significantly increase adherence to AL, not even among young children for whom the risk of malaria mortality is highest.…”
Section: Discussionmentioning
confidence: 90%
“…For example, patients may not understand how to correctly take the medication, 45,56-60 they may forget to take their pills, 18,56,58,59 they may be saving some pills for a future malaria episode, 45,56 or they may stop taking the medication once they feel better. 61,62 In our study, we found no relationship between literacy or education and adherence, and we also found that 91% of patients took the first two doses of AL with the correct number of pills at approximately the correct time (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mHealth, or mobile health, projects have shown to be increasingly successful in developing countries. Collecting health data (8)(9)(10), increasing access to health knowledge (11)(12)(13)(14), promoting provider quality (15)(16)(17), and increasing medication/appointment adherence (18)(19)(20) are a few ways in which mobile phones have successfully been used in developing countries to support health. In addition, rigorous evaluations have demonstrated mobile phone messages to be successful in supporting preventative healthcare (8,14,18,21,22) such as chronic disease prevention in Seychelles (23).…”
Section: Introductionmentioning
confidence: 99%